Audio-based digital biomarkers in diagnosing and managing respiratory diseases: a systematic review and bibliometric analysis - Vivianne Landry; Jessica Matschek; Roger Pang; Meghana Munipalle; Kenneth Tan; Jill Boruff; Nicole Y.K. Li-Jessen (European Respiratory Review)
Advances in wearable sensors and artificial intelligence have greatly enhanced the potential of digitised audio biomarkers for disease diagnostics and monitoring. In respiratory care, evidence supporting their clinical use remains fragmented and inconclusive. This study aimed to assess the current research landscape of digital audio biomarkers in respiratory medicine through a bibliometric analysis and systematic review (PROSPERO CRD 42022336730). MEDLINE, Embase, Cochrane Library and CINAHL were searched for references indexed up to 9 April 2024. Eligible studies evaluated the accuracy of sound analysis for diagnosing and managing obstructive (asthma and COPD) or infectious respiratory diseases, excluding COVID-19. A narrative synthesis was conducted, and the QUADAS-2 tool was used to assess study quality and risk of bias. Of 14 180 studies, 81 were included. Bibliometric analysis identified fundamental (e.g. “diagnostic accuracy”+“machine learning”) and emerging (e.g. “developing countries”) themes. Despite methodological heterogeneity, audio biomarkers generally achieved moderate (60–79%) to high (80–100%) accuracies. 80% of studies (eight out of ten) reported high sensitivities and specificities for asthma diagnosis, 78% (seven out of nine) reported high sensitivities and 56% (five out of nine) reported high specificities for COPD, and 64% (seven out of eleven) reported high sensitivity or specificity values for pneumonia diagnosis. Breathing and coughing were the most common biomarkers, with artificial neural networks being the most common analysis technique. Future research on audio biomarkers should focus on testing their validity in clinically diverse populations and resolving algorithmic bias. If successful, digital audio biomarkers hold promise for complementing existing clinical tools in enabling more accessible applications in telemedicine, communicable disease monitoring, and chronic condition management.